The call of the wild - London, Jack, 1876-1916. (London : Harper Press, 2011)
The classic tale of a dog who is part wolf as he eventually makes his peace with man in the wilderness of Northern Canada.
8.0
Young Adult
Young Adult
Keywords: Dogs -- Juvenile fiction; Wolves -- Juvenile fiction; Dogs -- Fiction; Wolves -- Fiction; Dogs -- Fiction; Wolves -- Fiction; Yukon -- Juvenile fiction; Yukon -- Fiction; Yukon -- Fiction